2012
DOI: 10.3126/ijosh.v2i1.4963
|View full text |Cite
|
Sign up to set email alerts
|

The Green Hazards: A Meta-Analysis of Green Tobacco Sickness

Abstract: Green Tobacco Sickness (GTS) has been one of the unexplored areas of occupational health safety. The condition mainly affects the tobacco harvesters. The condition is prevalent in Asian and South American tobacco harvesters. Although transient, the condition can affect multiple organ systems. The objective of this review is to extensively discuss the background, epidemiology, clinical features and measures to counter the problem.A literature search of Medline with terms such as “green”, “tobacco” and “sickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…It's mainly caused by handling green and fresh wet leaves of tobacco. The symptoms of tobacco workers that are reported in the current study are also reported by several studies among green tobacco workers [44,45,46].…”
Section: Discussionsupporting
confidence: 86%
“…It's mainly caused by handling green and fresh wet leaves of tobacco. The symptoms of tobacco workers that are reported in the current study are also reported by several studies among green tobacco workers [44,45,46].…”
Section: Discussionsupporting
confidence: 86%
“…[4][5][6][7] Previous studies have shown that dermal absorption of nicotine from plant surfaces gives rise to characteristic GTS symptoms. [8][9][10] GTS morbidity concerns nearly a quarter of tobacco workers, with typical symptoms including nausea, vomiting, headache, abdominal cramps, breathing difficulty, abnormal body temperature, pallor, chills, fluctuations in blood pressure and heart a r t i c l e rate, drenching sweats, and increased salivation. [1][2][3] GTS is a result of acute nicotine poisoning caused by dermal absorption of nicotine from mature tobacco plants.…”
Section: Introductionmentioning
confidence: 99%
“…Wearing socks was a risk factor for the development of GTS, in which was confirmed in this study. However, in another study that describes the use of water-resistant protective clothing as well as chemical-resistant gloves, plastic aprons, and rainwear with boots and socks, reduce the chances of developing GTS as it would decrease exposure nicotine (9) .…”
Section: Resultsmentioning
confidence: 99%
“…Nausea and weakness may occur within 15 minutes after contact with the skin (4) , with signs and symptoms usually occurring after work for 3 and 17 hours, and may vary. Diagnosis is based on the triad: presence of compatible signs and symptoms such as those already listed, history of exposure to tobacco culture and high levels of nicotine by measuring the cotinine level (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation